Integration of flow battery for resilience enhancement of advanced distribution grids. (July 2019) - Panwar, Mayank; Chanda, Sayonsom; Mohanpurkar, Manish; Luo, Yusheng; Dias, Fernando; Hovsapian, Rob; Srivastava, Anurag K.
Highlights: Real-time resiliency framework is used for analysis and sizing of energy storage. Flow battery hardware-characterized dynamic data used for real-time simulations. Reconfiguration algorithms as advanced operation functionality in grids with DERs. Abstract: This paper presents a real-time simulation and hardware-based approach for systematic integration of Distributed Energy Resources (DERs) in advanced distribution grids with a special focus on resilience. Advanced distribution grids are considered to be functionally more sophisticated than traditional ones. The desirable advanced functionalities include – reconfiguration, real-time sensing, DERs, self-healing, etc. Some of these functionalities are currently being realized by microgrids as well. However, it is not feasible to convert each section of a distribution grid into a microgrid, but can be instituted with functionalities by design and controls at relatively lower costs. Interconnection of DERs, including energy storage to improve reliability and resilience is presented in details. Resilience of distribution grids is gaining greater importance and research towards enhancing it utilizing DERs is a key area. A real-time resilience framework with Analytical Hierarchical Processes (AHP) is developed that adapts to changing configurations, DERs, switching operations, grid conditions, etc. to provide an accurate and adoptable composite resilience metric. This framework and the composite resilience metric can play a unique role in operational and design decisions for operating future distribution grids. Advanced functionalities such as scenario-based reconfiguration in distribution grids are considered, with resilience metrics as performance criteria for choosing a preferred combination. Simulations are performed using Digital Real-Time Simulator (DRTS) and characterized response of flow battery validated against actual flow battery hardware is imposed to provide realistic results. Reconfiguration program is interfaced with DRTS for bi-directional real-time communication. Key contributions include enhancement of resilience of distribution grids using energy storage system under dynamic operating conditions.